If \(f(x) = x^2\), then \(af(x) = a(x^2)\). This tells us that we need to multiply each of the \(y\) coordinates on the graph by \(a\) in order to stretch the original graph. Looking at some ...
In this instance, x=0. Do the same for x=1, x=2, x=3 and x=4. Image caption, STEP 3 - Draw a graph and label the x axis 1 to 4 and the y axis 1 to 9. A linear equation is represented as a line graph.
Find \(\ds \lim_{h\to 0}\frac{f(1+h)-f(1)}{h}\) where \(\ds f(x)=\frac{3x+1}{x-2}\text{.}\) What does the result in (a) tell you about the tangent line to the graph ...